2013
DOI: 10.1002/jmri.24216
|View full text |Cite
|
Sign up to set email alerts
|

R2* as a surrogate measure of ferriscan iron quantification in thalassemia

Abstract: R2* values can predict HIC determined by FerriScan using a linear calibration curve. This technique may provide a potentially cost-saving alternative for hepatic iron determination and improve acceptance by referring physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
2
20
1
Order By: Relevance
“…Garbowski et al directly compared T2* MRI with biopsy and indirectly against R2 generated LIC [11]. Chan et al has performed a MRI retrospective analysis [12] and Wood et al prospectively compared R2 and R2* derived LIC in both Thalassaemia major and Sickle cell disease patients [10]. These studies observed a close relationship between R2* and R2 LIC however the relationships were not as robust as demonstrated in our study.…”
Section: Discussioncontrasting
confidence: 65%
“…Garbowski et al directly compared T2* MRI with biopsy and indirectly against R2 generated LIC [11]. Chan et al has performed a MRI retrospective analysis [12] and Wood et al prospectively compared R2 and R2* derived LIC in both Thalassaemia major and Sickle cell disease patients [10]. These studies observed a close relationship between R2* and R2 LIC however the relationships were not as robust as demonstrated in our study.…”
Section: Discussioncontrasting
confidence: 65%
“…Quantitative measurements were only performed on 12 mice (6 groups of n = 2), all of which had measured LICs of less than 0.8 mg/g of wet tissue. Other studies conducted on human liver tissues have reported significantly higher LIC measurements, with a maximum around 7 mg/g of wet tissue . Therefore, in order to more accurately develop a standardized susceptibility‐to‐LIC conversion factor, a larger sample size covering a wider range of LIC values should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…A number of MRI‐based LIC quantification methods have been proposed as alternatives to FerriScan . However, strong evidence of a technique's validity would be required before it could be considered as an acceptable alternative.…”
mentioning
confidence: 99%